Review and comparison study of hybrid diesel/solar/hydro/fuel cell energy schemes for a rural ICT Telecenter - M.O., Abdullah; V.C., Yung; A.K., Othman; K.B. Ab. Hamid, Ab. Hamid; J., Tarawe (Elsevier Ltd., 2010)
In this paper, the rural electrification study of an ICT Telecenter in particular reference to the Kelabit Highland of Sarawak is presented. The use of diesel generator and its associated environmental implications is first discussed. The cost-effectiveness of the present solar PV system and the solar/hydro schemes for rural electrification of the rural ICT are evaluated employing the HOMER simulation software, considering sustainability factors such as system efficiency, weather, fuel costs, operating and maintaining costs. Subsequently, simple novel Hybrid Energy Performance Equations and the associated Energy Performance Curves are derived and introduced, respectively, which provide a visualization model, simplifying hybrid system analysis. Results obtained in this study have shown that combined power schemes is more sustainable in terms of supplying electricity to the Telecenter compared to a stand-alone PV system due to prolong cloudy and dense haze periods. The hybrid systems can have efficiency range of w15%–75% compared to PV stand-alone of only w10%, indicating hybrid systems are more reliable and sustainable – in minimizing both energy losses and excess energy.